(untitled) - Matsui, Yoshiya (Singapore, 1993)
At present, although most of the optical design processes are automated with the aid of computer software, the fundamental question of how we can generate the initial optical configuration such that it can be dealt with by the computer remains. The answer can only be found in applying techniques based on the aberration theory. Previous works have explored this subject matter. None, however, has covered the full extent of first deriving the aberration theory and then illustrating with the help of various kinds of actual examples how it can be applied effectively to practical design problems. This book is significant in its attempt to put theory into practice for the first time to provide new insight and knowledge to its readers.
Keywords: Quang sai,Aberration